Preserving Urban Roots: The Case of Shakhari Bazaar, Dhaka, Bangladesh - Niger, Maher (Nakhara : Journal of Environmental Design and Planning, 2013)
This paper discusses how conservation activities in an historic urban settlement can be carried out in the most supportive manner. Conservation is not only preserving a few historic buildings but rather preserving the urban cultural heritage and the environment that gave birth to city culture. The importance of “Preserving Urban Roots”, that is protecting historical cities through preservation, restoration and revitalization, is a universally accepted matter, but in reality it is a neglected issue. Historic urban quarters of old cities are often strongly characterized by environmental degradation and many of them are now suffering serious destruction and are losing their characteristics due to negligence. Shakhari Bazaar in Dhaka is a signifi cant historical quarter, a coherent neighborhood of richly detailed buildings, where a traditional community has lived for centuries, but the existing environment of this area is vulnerable. This study is aimed at understanding the various processes of conservation in this historic urban settlement. The processes include having appropriate attitudes, developing greater community participation, preparing detailed documentation of the study area, identifying core/peripheral aspects of culture and built-form, and cultivating fi nancial and institutional support. The study also makes the case for providing necessary services in the area and developing the total area as an ideal conserved area, not only by restoring existing building but also by preserving the traditional culture and heritage, shape and size of this area.